CONCEPTUALIZING THE INTERDEPENDENCE OF THE PHENOMENA OF «STATE COMPETITIVENESS» AND «NATIONAL SECURITY» - SYTNYK, Hryhorii; TARAN, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article is devoted to the analysis of theoretical and practical aspects of the interdependence of the phenomena of «state competitiveness» and «national security».The aim of the research is to reveal the essence, components, indicators, factors, mechanisms, challenges, threats, prospects and strategies of ensuring these phenomena, as well as their dynamics and transformation in the conditions of globalization, digitalization, democratization, innovation.To achieve the research goal, the authors set the following tasks: to analyze the scientific literature on state competitiveness and national security, to compare the level of state competitiveness and national security in different countries and regions, to identify the main challenges and threats for state competitiveness and national security in modern conditions, to propose ways of increasing state competitiveness and national security of Ukraine.The authors use analysis and synthesis of scientific literature, statistical data, normative-legal acts, documents of international organizations, comparative and historical, systemic and complex, logical and critical methods of research.The authors conclude that state competitiveness and national security are interrelated and interdependent phenomena that determine the status, role and prospects of the state in the world community, and that to increase state competitiveness and national security in the future, it is necessary to implement comprehensive reforms and modernization in all spheres of life. The main strategic direction of Ukraine in the field of ensuring national security is to create sufficient own capabilities as a basis for ensuring its own security and resilience.
Keywords: concept; competitiveness; state; national security; principles; goals; strategies; models; mechanisms of public administration; digitalization; optimization